2009
DOI: 10.1001/jama.2008.976
|View full text |Cite|
|
Sign up to set email alerts
|

Treating Drug Abuse and Addiction in the Criminal Justice System

Abstract: Despite increasing evidence that addiction is a treatable disease of the brain, most individuals do not receive treatment. Involvement in the criminal justice system often results from illegal drug-seeking behavior and participation in illegal activities that reflect, in part, disrupted behavior ensuing from brain changes triggered by repeated drug use. Treating drug-involved offenders provides a unique opportunity to decrease substance abuse and reduce associated criminal behavior. Emerging neuroscience has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
403
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(423 citation statements)
references
References 80 publications
(82 reference statements)
12
403
1
7
Order By: Relevance
“…52,53 Whether or not criminal justice involvement exacerbates disparities in health outcomes, opportunities may exist to mitigate health disparities at four points along the criminal justice continuum: (1) entry into the correctional system, (2) during custody, (3) in the transition from prison to the community, and (4) during subsequent community supervision, such as parole and probation. At entry into the correctional system, health providers may provide evidence-based health screening based on both standard recommendations (e.g., hypertension, hypercholesterolemia) and for specific issues of high prevalence/ concern in minority or incarcerated populations (e.g., tuberculosis, HIV, hepatitis C).…”
Section: The Criminal Justice System As An Opportunity To Decrease Hementioning
confidence: 99%
“…52,53 Whether or not criminal justice involvement exacerbates disparities in health outcomes, opportunities may exist to mitigate health disparities at four points along the criminal justice continuum: (1) entry into the correctional system, (2) during custody, (3) in the transition from prison to the community, and (4) during subsequent community supervision, such as parole and probation. At entry into the correctional system, health providers may provide evidence-based health screening based on both standard recommendations (e.g., hypertension, hypercholesterolemia) and for specific issues of high prevalence/ concern in minority or incarcerated populations (e.g., tuberculosis, HIV, hepatitis C).…”
Section: The Criminal Justice System As An Opportunity To Decrease Hementioning
confidence: 99%
“…Esse foco junto aos profissionais nos serviços é visto na literatura como uma estratégia para oferecer diferentes ferramentas e alternativas para otimizar o processo ensino-aprendizagem (BARROS, et al, 2008;CHANDLER;FLETCHER;, VOLKOW, 2009;GALLASSI;DOS SANTOS, 2013). Porém, observa-se pouco espaço formativo das IES na educação superior, base para construção de competências para a atuação profissional.…”
Section: Resultsunclassified
“…Brain imaging studies shed light on addiction pathways and changes in the structure and functioning of the brain due to substance use [13]. Studies showed that repeated exposure to drugs created neural connections to the substances of abuse and associated stimuli, which explained why drug-related stimuli served as triggers for relapse.…”
Section: Scientific Developments In Addiction and Treatmentmentioning
confidence: 99%